Prevalence of non-alcoholic fatty liver disease in type-2 diabetes mellitus patients - Patel, Hardik; Verma, Yadav Narain (International Journal of Research in Medical Sciences, 2018)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common chronic condition of which diabetic fatty liver accounts for a large proportion, with 50 to 75% of the subjects demonstrating fat in the liver on ultrasound. As a result of epidemic increase in diabetes mellitus, hypertension, obesity and hyperlipidemia, the prevalence of NAFLD is increasing worldwide. Methods: A study was conducted on a total 100 type-2 diabetes mellitus patients attending Geetanjali Medical College and Hospital, Udaipur, Rajasthan. Patients with known chronic liver disease and history of alcohol intake were excluded. These patients were evaluated by abdominal ultrasonography to determine the presence of fatty liver. They were divided into fatty liver group and non-fatty liver group; and were further evaluated by measurement of body mass index, Central obesity, HbA1c and lipid profile. The data obtained was analyzed using SPSS version 20.0. Results: Of the 100 diabetic patients enrolled in this study, 64 (64%) presented with NAFLD. The highest prevalence of NAFLD was recorded in the age group of 50-59 years at 37.5%. The prevalence rate among males (65.62%) was higher than for females (34.38%). A comprised NAFLD patients (64%) and Non-NAFLD patients (34%). Conclusions: This study revealed that the NAFLD is a vital part of cluster of abnormalities such as dysglycemia, dyslipidemia, hypertension and obesity. Age and duration of diabetes are also important contributing factors in occurrence of NAFLD.